Mitochondrial Breast Cancer Resistant Protein Sustains the Proliferation and Survival of Drug-Resistant Breast Cancer Cells by Regulating Intracellular Reactive Oxygen Species - Zhang, He; Han, Xingxing; Wang, Zhaosong; Wang, Zhiyong; Cui, Yanfen; Tian, Ran; Zhu, Yuying; Han, Baoai; Liu, Hui; Zuo, Xiaoyan; Ren, Sixin; Tian, Jianfei; et al. (Frontiers in Cell and Developmental Biology, 2021)
ATP-binding cassette (ABC) transporter family are major contributors to the drug resistance establishment of breast cancer cells. Breast cancer resistant protein (BCRP), one of the ABC transporters, has long been recognized as a pump that effluxes the therapeutic drugs against the concentration gradient. However, recent studies suggest that the biological function of BCRP is not limited in its drug pump activity. Herein, the role of BCRP in the proliferation and survival of drug-resistant breast cancer cells was investigated. We found that BCRP is not the major drug pump to efflux epirubicin in the resistant cells that express multiple ABC transporters. Silencing of BCRP significantly impairs cell proliferation and induces apoptosis of the resistant cells in vitro and in vivo. RNA-sequencing and high-throughput proteomics suggest that BCRP is an inhibitory factor of oxidative phosphorylation (OXPHOS). Further research suggests that BCRP is localized in the mitochondria of the resistant cells. Knockdown of BCRP elevated the intracellular reactive oxygen species level and eventually promotes the cell to undergo apoptosis. This study demonstrated that BCRP exerts important onco-promoting functions in the drug-resistant breast cancer cells independent of its well-recognized drug efflux activity, which shed new light on understanding the complex functional role of ABC transporters in drug-resistant cells.